A cryo-TSEM with temperature cycling capability allows deep sublimation of ice to uncover fine structures in thick cells - Jiro Usukura (Nature Portfolio, 2021)
Abstract The scanning electron microscope (SEM) has been reassembled into a new type of cryo-electron microscope (cryo-TSEM) by installing a new cryo-transfer holder and anti-contamination trap, which allowed simultaneous acquisition of both transmission images (STEM images) and surface images (SEM images) in the frozen state. The ultimate temperatures of the holder and the trap reached − 190 °C and − 210 °C, respectively, by applying a liquid nitrogen slush. The STEM images at 30 kV were comparable to, or superior to, the images acquired with conventional transmission electron microscope (100 kV TEM) in contrast and sharpness. The unroofing method was used to observe membrane cytoskeletons instead of the frozen section and the FIB methods. Deep sublimation of ice surrounding unroofed cells by regulating temperature enabled to emerge intracellular fine structures in thick frozen cells. Hence, fine structures in the vicinity of the cell membrane such as the cytoskeleton, polyribosome chains and endoplasmic reticulum (ER) became visible. The ER was distributed as a wide, flat structure beneath the cell membrane, forming a large spatial network with tubular ER.